Environmental developments in Malaysia : a review on challenges and opportunities ahead to eco-innovate / J. S. Keshminder - Keshminder, J. S. (Universiti Teknologi MARA, Perak, 2018)
Climate change is taking a toll on governments around the world as it is a challenge to determine the most effective environmental policies to promote eco-innovation. This paper investigates the environmental developments that have taken place in Malaysia to address the challenges and opportunities to promote eco-innovation. Past and present literature was qualitatively analyzed to prepare the environmental review for this study. The results suggest that Malaysia is implementing more superior environmental policies to promote eco-innovation. Command and control-based approach is slowly being replaced with guided self-regulation approach and cradle-to-cradle principle. The evidence suggests several shortcomings where the large industries are not given adequate focus under the wnvironmental agenda and a holistic eco-innovation framework is yet to emerge.